1977
DOI: 10.1111/j.1476-5381.1977.tb08427.x
|View full text |Cite
|
Sign up to set email alerts
|

A Conformational Analysis for Leucine‐enkephalin Using Activity and Binding Data of Synthetic Analogues

Abstract: Leucine‐enkephalin and some analogues were assayed for activity in vitro on the mouse vas deferens and for binding to opiate receptors from rat brain. The experimental data were analysed in terms of the stringency for glycine, a D‐amino acid or an L‐amino acid at each position in the peptide. The observed configurational specificity was compared with the stringency that would be predicted to occur if enkephalin adopted certain hydrogen‐bonded conformations at the receptor. A small subset of the conformations e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“…Compounds 3, 4, and 6 were found to bind DOPR with modest affinity, a finding consistent with our observation that these compounds were less efficient than Leu 5 -enkephalin and compound 1 at promoting DOPR internalization (Figures 6 and 7) and ERK1/2 phosphorylation (Figure 8 -enkephalin strongly reduces its affinity and activity for DOPR (17,18). In fact, it is known that the phenyl side chain of the L-Phe 4 residue of Leu 5 -enkephalin is critical for its biological activity (17) and that Leu -enkephalin were shown to bind and activate DOPR similarly (17,18). Still, the slightly better affinity of compound 6 led us to hypothesize that this compound contains a D-Leu at position 5 while compound 4 contains an L-Leu at the same position.…”
Section: Binding Properties Of Enkephalin Derivativessupporting
confidence: 76%
See 3 more Smart Citations
“…Compounds 3, 4, and 6 were found to bind DOPR with modest affinity, a finding consistent with our observation that these compounds were less efficient than Leu 5 -enkephalin and compound 1 at promoting DOPR internalization (Figures 6 and 7) and ERK1/2 phosphorylation (Figure 8 -enkephalin strongly reduces its affinity and activity for DOPR (17,18). In fact, it is known that the phenyl side chain of the L-Phe 4 residue of Leu 5 -enkephalin is critical for its biological activity (17) and that Leu -enkephalin were shown to bind and activate DOPR similarly (17,18). Still, the slightly better affinity of compound 6 led us to hypothesize that this compound contains a D-Leu at position 5 while compound 4 contains an L-Leu at the same position.…”
Section: Binding Properties Of Enkephalin Derivativessupporting
confidence: 76%
“…The Tyr-Gly-Gly-Phe//D-Leu stereochemistry was attributed to 6 because it is slightly more active than 4, similar to TyrGly-Gly-Phe-D-Leu, which is more active toward DOPR than Leu 5 -enkephalin (cf. Table 1) (17,18). Admittedly, this assumption is only based on comparative binding and activity with previous studies and remains to be confirmed by X-ray analysis.…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…The μ-opioid receptor is located in the central nervous system (CNS), while the δ-opioid receptor is related the peripheral nervous system. 3,4 Their endogenous ligands, "opioids" (enkephalins, endorphins, dynorphins, and endomorphins) are involved in several important physiological functions, including nociception, autonomic reflexes, neuroendocrine effects, and thermoregulation. 5,6 Several analgesic drugs, including morphine, are commonly used to reduce pain stemming from cancer or nervous damage.…”
Section: Introductionmentioning
confidence: 99%